Molecular orbital composition and its effect on electron-impact ionization cross sections of molecules: A comparative study - Zhong, Linlin; Wang, Xiaohua; Rong, Mingzhe (Physics of plasmas, 2018)
The composition of molecular orbitals (MO) is the key parameter in the calculation of electron-impact ionization cross sections (Qion) of a molecule using the Deutsch-Märk method. There are a few theoretical approaches for determining the MO composition, such as Mulliken-like methods [including Mulliken analysis, Stout-Politzer (SP) analysis, and c-squared population analysis] and natural atomic orbital (NAO) method. However, almost all the previous works chose the Mulliken analysis without explanation, which is arbitrary and can lead to meaningless results in some cases. In order to give a guide on how to select an appropriate method for the MO composition and reveal the effect of the MO composition on Qion, a comparative study is presented in this work based on the results of quantum chemical computation. It is found that the Mulliken-like and NAO methods output similar MO compositions for occupied orbitals and much different MO compositions for virtual orbitals. The results by the Mulliken and SP methods are not always in the range of 0%–100% for virtual orbitals. Moreover, the Mulliken-like methods are more dependent on basis sets than the NAO method. This basis-set dependence exists not only in the MO composition but also in ionization cross sections of molecular shells. As a result, we conclude that the NAO method is the best choice for the MO composition in calculating the Qion of a molecule.